How to Conduct a Metaevaluation?: A Metaevaluation Practice - Kerimoglu, Esra; Ulker, Muazzez Nihal Oyku; Berk, Saban (UNIV TORONTO PRESS INC, 2023)
A metaevaluation is a quality cross-check to examine the conduct of an evaluation and validate the results. Of the few metaevaluation studies, almost none have reported on the metaevaluation procedure through a practical example evaluation. This study reports on the strengths and weaknesses of a program evaluation study in terms of the four main standards: utility, feasibility, propriety, and accuracy. It includes a metaevaluation process that involves both quantitative and qualitative analysis of data from eight meta-evaluators. It was found that while the evaluation study had very good utility and accuracy standards, the feasibility and propriety standards were only fair.
Keywords: metaevaluation; metaevaluation practice; evaluating the evaluation; program evaluation; QUALITY; MANAGEMENT; Social Sciences - Other Topics